Beta-adrenoreceptor mechanisms in essential tremor; a double-blind placebo controlled trial of metoprolol, sotalol and atenolol. Issue 8 (August 1983) - Leigh, P N; Jefferson, D; Twomey, A; Marsden, C D
Abstract : In order to elucidate the mode of action of beta-adrenoreceptor antagonists in essential tremor, the efficacy of chronic oral administration of metoprolol, atenolol and sotalol was compared in a randomised, double-blind placebo controlled trial in twenty-four patients. Only sotalol proved superior to placebo on both subjective and "objective" assessments. Metoprolol and sotalol produced comparable degrees of beta-adrenoreceptor antagonism as judged by the blockade of standing tachycardia. Atenolol, in the dose used, produced a trend towards a greater cardiac chronotropic effect. These findings provide no support for the concept that central or peripheral beta 1-adrenoreceptor mechanisms are important in essential tremor. The beneficial effect of beta-adrenoreceptor antagonists may be mediated predominantly through peripheral beta 2-adrenoreceptor mechanisms.